Treatment on Distoversion of Upper Central Incisor and Transposition of the Maxillary Upper Right Canine and Lateral Incisor Orthodontic (Phase One) - Eriza Juniar (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2018)
Background: Tooth transposition is a rare and severe positional anomaly that may create many orthodontic problems from both esthetic and functional points of view. In this case report, the orthodontic management of distoversion upper central incisor and transposition of the upper right canine and lateral incisor. The patient was treated with a fixed appliance for 4 months. At this moment the central incisor has already corrected, lateral incisor has also erupted and aligned. Patient management should be continued with phase two treatment to correct the transposition of canine.